Pregnancy Complications and Outcomes Among Women With Congenital Heart Disease in Beijing, China - Liu, Yang; Li, Yanna; Zhang, Jun; Zhao, Wenjuan; Bao, Zhaoliang; Ma, Xiaolong; Zhao, Yichen; Zhao, Cheng; Liu, Kemin; Ye, Qing; Su, Lixiao; Yang, Yao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To conduct a comparative analysis of the complications and outcomes in pregnant women with and without congenital heart disease (CHD) in Beijing, China. Methods We compared pregnancy-related complications and outcomes experienced by women with and without CHD throughout 19,424 deliveries in Beijing Anzhen Hospital between 2010 and 2019, including cardiovascular and obstetric factors, fetal events, delivery methods, and other complications over a mean 5-years post-delivery follow-up period. Results There were 1,040 women with CHD (5.35% of all deliveries). Compared to women without CHD, these women had longer hospital stays (7.83 ± 4.65 vs. 4.93 ± 3.26 days) and a higher death rate (1.92 vs. 0.02%). They also had a greater risk of comorbidities, including pre-term delivery (odds ratio: 13.65 vs. 6.71), heart failure (odds ratio: 4.90 vs. 0.40), and arrhythmia (odds ratio 12.69 vs. 4.69). Pulmonary hypertension, New York Heart Association functional class III IV, and no congenital heart disease surgery prior to pregnancy were associated with adverse events such as cesarean section, pre-term delivery, and heart failure. The fetuses of mothers with CHD were more likely to be born pre-term (odds ratio: 13.65 vs. 6.71) and have low birth weight (odds ratio: 8.56 vs. 4.36). Eleven infants (1.82%) born to mothers with CHD and four infants (0.64%) born to mothers without CHD were diagnosed with CHD. Conclusions Women with CHD generally increase maternal and infant risk during pregnancy and the perinatal period. Pulmonary hypertension, decrease in cardiac function, and no previous CHD surgery increase the risk in women with CHD. Greater attention should be paid to pregnant women with CHD and their fetuses, newborns.